Transformation of Administration in Modern Islamic Boarding Schools (Pondok Pesantren) in Indonesia - Soleh, Muhamad Ibnu (Academia Publication, 2024)
The transformation of administrative processes in modern Islamic boarding schools (pondok pesantren) has become increasingly essential in response to the rapid advancements in digital technology. This study aimed to examine the efficiency of administrative digitalization in modern pesantren located on Java Island. The study utilized a qualitative approach, using data collection methods such as in-depth interviews, observations, and document analysis. The results showed that administrative digitalization had significantly improved the operational efficiency of pesantren, particularly in areas such as data management, communication, and decision-making processes. The adoption of digital technology had streamlined administrative procedures, enhanced transparency, and increased the accuracy of data, while also reducing the administrative burden. Despite these benefits, the study identified several challenges, including limited technological infrastructure and resistance to change among administrative staff. In conclusion, this study suggested that administrative digitalization is a crucial step in supporting the modernization of pesantren and improving their overall operational efficiency. Recommendations are made for the development of more robust technological infrastructure and the provision of training for administrative staff to ensure the effective implementation of digital technology in daily operations.